God, chance & necessity - Ward, Keith, 1938- (Oxford, One World, 1996)
The 'new materialism' argues that science and religious belief are incompatible. This book considers such arguments from cosmology (Stephen Hawking, Peter Atkins), from biology (Charles Darwin, Richard Dawkins) and from sociobiology (Michael Ruse), and exposes a number of fallacies and weaknesses. With a carefully argued, point-by-point refutation of scientific atheism, God, Chance and Necessity shows that modern scientific knowledge does not undermine belief in God, but actually points to the existence of God as the best explanation of how things are the way they are. Thus it sets out to demolish the claims of books like The Selfish Gene, and to show that the overwhelming appearance of design in nature is not deceptive
The origin of the universe -- Something for nothing; a dubious deal -- Is there any point? Where the universe is going -- Darwin and natural selection -- The metaphysics of theism -- The elegance of the life-plan -- Evolution and purpose -- Brains and consciousness -- The future of evolution -- Suffering and goodness
Includes bibliographical references (pages 205-207) and index
Keywords: Religion and science; Materialism -- Religious aspects -- Christianity; Religion and Science